Computerized psychiatric interviews: can they help to improve medical care? - Tirol, TirolRenata; Menezes, Paulo Rossi (São Paulo Medical Journal, 1998)
Studies on psychiatric disorders in Brazil have shown high prevalence rates, both in the community and in primary care centers. However, psychiatric assessments carried out by interviewers have some inherent problems which influence inter-observer reliability. There is great potential for the use of computerized interviews. This article discusses some advantages of this kind of assessment, and indicates a need for investigation into its applicability to Brazilian health care settings.